1979
DOI: 10.1016/s0003-4975(10)63123-2
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal Agenesis

Abstract: Tracheal agenesis is a rare cause of respiratory distress in the neonatal period. Temporary survival depends on ventilation through the esophagus. Thirty-eight case reports of tracheal agenesis (including one from this institution) have appeared in the literature. In this paper, we present the case reports of our 2 patients and review the literature. Tracheal agenesis is associated with a wide variety of congenital anomalies, the most frequent being ventricular septal defect. A new classification encompassing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

1985
1985
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 20 publications
0
35
0
1
Order By: Relevance
“…Tracheal agenesis appears to have been described first by Payne [ 19001; subsequently 41 other patients were reported [Walcher, 1928;Fritz, 1933;Benesova and Peter, 1934;Marek, 1940;Morison, 1949;Milles and Dorsey, 1950;Kessel and Smith, 1953;Sandison, 1955;Hempel, 1956;Devenis and Otis, 1957;Onarir and Sariyalcin, 1961;Floyd et al, 1962;Witzleben, 1963;Fonkalsrud et al, 1963;McCracken et al, 1964;Devi and More, 1966;Stowens, 1966;Colavecchio, 1968;Lyons and Bruce, 1968;Eimer, 1969;Joshi, 1969;McNie and Pryse-Davies, 1970;Altman et al, 1972;Hopkinson, 1972;Hong et al, 1973;Effman et al, 1975;Chaurasia, 1976;Warfel, 1976;Donovan and Friedman, 1979;Far0 et al, 1979;Buchino et al, 1982; DFC:23 24 Evans, Reggin, and Greenberg Haupt and Edwards, 19831. In these cases tracheal agenesis was partial or total and various classifications of this malformation have been described [Floyd et al, 1962;Faro et al, 1979;Kluth, 19761.…”
Section: Pathogenesismentioning
confidence: 99%
“…Tracheal agenesis appears to have been described first by Payne [ 19001; subsequently 41 other patients were reported [Walcher, 1928;Fritz, 1933;Benesova and Peter, 1934;Marek, 1940;Morison, 1949;Milles and Dorsey, 1950;Kessel and Smith, 1953;Sandison, 1955;Hempel, 1956;Devenis and Otis, 1957;Onarir and Sariyalcin, 1961;Floyd et al, 1962;Witzleben, 1963;Fonkalsrud et al, 1963;McCracken et al, 1964;Devi and More, 1966;Stowens, 1966;Colavecchio, 1968;Lyons and Bruce, 1968;Eimer, 1969;Joshi, 1969;McNie and Pryse-Davies, 1970;Altman et al, 1972;Hopkinson, 1972;Hong et al, 1973;Effman et al, 1975;Chaurasia, 1976;Warfel, 1976;Donovan and Friedman, 1979;Far0 et al, 1979;Buchino et al, 1982; DFC:23 24 Evans, Reggin, and Greenberg Haupt and Edwards, 19831. In these cases tracheal agenesis was partial or total and various classifications of this malformation have been described [Floyd et al, 1962;Faro et al, 1979;Kluth, 19761.…”
Section: Pathogenesismentioning
confidence: 99%
“…In 1962, Floyd [2] collected 13 cases including his own case, and classified them into three types; type I is atresia of part of trachea with short distal trachea, type II is complete tracheal atresia but normal bronchi and bifurcation, and type III has no trachea, but bronchi arise from the esophagus directly. In 1979, Faro et al reported a more detail classification of tracheal agenesis (7 types) based on the literature review [3]. To our best knowledge, 144 cases of tracheal agenesis, including 19 of type I, 87 of type II and 38 of type III, have been reported in the English literature [4][5][6][7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Tracheal agenesis and esophageal atresia in rats have been recently associated with Nog, a gene encoding a bone morphogenetic protein antagonist [6]. Two classification schemes are available [7,8].…”
Section: Discussionmentioning
confidence: 99%